Evaluation of the anti-obesity effect of Sambucus nigra L. (elderberry) and Vitex agnus-castus L. (chasteberry) extracts in high-fat diet-induced obese rats - Ulusoy, Şeyma; İnal, Ebrar; Küpeli Akkol, Esra; Çiçek, Mahmut; Kartal, Murat; Sobarzo-Sánchez, Eduardo (Frontiers in Pharmacology, 2024)
The aim of this study was to investigate the effects of Sambucus nigra L. and Vitex agnus-castus L. plants on obesity in vivo. Extracts were prepared from S. nigra leaves, flowers, fruits and from V. agnus-castus leaves, flowers, and fruits using 100% water and 70% ethanol. The total phenol and flavonoid contents of the extracts were quantified spectrophotometrically. The findings revealed that the ethanol extracts of V. agnus-castus and S. nigra flowers had the highest phenolic content, while the ethanol extracts of S. nigra flowers and V. agnus-castus leaves had the highest flavonoid content. Qualification and quantification of the phenolic contents of the extracts were carried out using liquid chromatography-high resolution mass spectrometry (LC-HRMS) analyses. The study investigated the effects of various extracts on plasma levels of leptin, insulin, triiodothyronine (T3), thyroxine (T4), triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL) and lipase enzyme in obesity-induced rats. The results showed that the ethanol extract of V. agnus-castus flowers, as well as the ethanol and water extracts of V. agnus-castus leaves, resulted in body weight reduction in rats with obesity. Additionally, these extracts were found to decrease serum levels of LDL, triglycerides, leptin, lipase, TNF-α, and IL-1 while increasing levels of HDL and adiponectin. The LC-HRMS results demonstrated that all three extracts exhibited relatively high concentrations of luteolin-7glycoside and kaempferol, in comparison to the other extracts. The ethanol extract of V. agnus-castus flowers contained 653.04 mg/100 g of luteolin-7-glycoside and 62.63 mg/100g of kaempferol. The ethanol extract of V. agnus-castus leaves contained 1,720.26 mg/100 g of luteolin-7-glycoside and 95.85 mg/100 g of kaempferol. The water extract of V. agnus-castus leaves contained 690.49 mg/100 g of luteolin-7-glycoside and 194.41 mg/100 g of kaempferol. The study suggests that the ethanol extract of V. agnus-castus flowers and leaves, as well as the water extract of V. agnus-castus leaves, may have potential benefits in treating obesity. However, further controlled clinical studies are necessary to evaluate the clinical efficacy of V. agnus-castus in treating obesity and investigate the in vivo anti-obesogenic effects of luteolin-7-glycoside and kaempferol separately, both in their pure form and in combination.